Facilitating co-research: lessons learned from reflection forms within three participatory action research projects - Helga Emke; Ann Vandendriessche; Mai Chinapaw; Benedicte Deforche; Maïté Verloigne; Teatske Altenburg; Manou Anselma (BMC, 2024)
Abstract Background Mutual learning and shared decision-making are key elements of Participatory Action Research (PAR), highlighting the important role of the facilitator to support this. This study aims to illustrate how a facilitator can contribute to successful PAR sessions based on the reflection of three PAR projects. Methods Participatory sessions took place with adolescents for 3-4 school years. After each session (n = 252 sessions across three projects), facilitators filled in a reflection form that assessed the group process and their facilitating role. Facilitators independently coded a selection of 135 reflection forms partly deductive and partly inductive based on core PAR principles derived from a pragmatic literature search. Results A well-prepared session - for example, including active and creative participatory methods and a clearly stated goal - contributed to efficiency and the necessary flexibility. Making agreements, making sure everyone is heard and taking 'fun-time' appeared important for creating and maintaining a safe, functional and positive atmosphere. Finally, facilitators needed to encourage co-researchers to take the lead and adapt to the group dynamics, to ensure ownership and shared decision-making. Conclusion In-depth qualitative analyses of a standardized reflection form used in three different PAR projects resulted in various lessons to support facilitators in collaborating with co-researchers in PAR projects.